The Relationship Between Motivation and Cadre Performance in the Healthy Fund Program in the Puskesmas Working Area Lhok Bengkuang, South Aceh District - Yasni, Hilma; Orisinal; Irwan, Syam; Rasima; Julissasman (International Journal of Multidisciplinary Sciences and Arts, 2023)
Dana sehat (Healthy fund) is very important for the community because it can ease the burden of citizen, the majority of family living in Darussalam is catagorized as low income family whose wage is below the minimum province level. However, Dana Sehat requires high dedication from the managers. This study aimed for finding out the corelation between motivation and cadres working performance who participate in Dana Sehat program in the area of Puskesmas (comunity helath center) Lok Bengkuang in Aceh Selatan Regency. This is a corelational study with cross sectional design. The research population comprised of 39 cadres who participate in Dana Sehat program. The sampling tecnique used is total sampling. Data is collected using question. Then it is analyzed using chi square test. The result of research showed that motivation in Dana Sehat program is in low category as many as 22 people (56.4%), cadres’ performance in Dana Sehat program is less than 26 people (66.7%). The result of chi square test showed that p-value =0.004 (?=0.05), to cadres who participate in Dana Sehat program in work area of Puskesmas Lhok Bengkuang in Aceh Selatan Regency. It is recommended that the cadres who are working area of the Puskesmas to obtain and knowledge about the Dana Sehat Program.